2020
DOI: 10.3390/cells9092085
|View full text |Cite
|
Sign up to set email alerts
|

Development of Feline Ileum- and Colon-Derived Organoids and Their Potential Use to Support Feline Coronavirus Infection

Abstract: Feline coronaviruses (FCoVs) infect both wild and domestic cat populations world-wide. FCoVs present as two main biotypes: the mild feline enteric coronavirus (FECV) and the fatal feline infectious peritonitis virus (FIPV). FIPV develops through mutations from FECV during a persistence infection. So far, the molecular mechanism of FECV-persistence and contributing factors for FIPV development may not be studied, since field FECV isolates do not grow in available cell culture models. In this work, we aimed at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…This suggested that mesenchymal-like cell types are essential for cat enteroid growth. Recently, Tekes et al reported to have generated colon-derived organoids and studied host–pathogen interactions and immune response against feline enteric coronavirus [ 100 ].…”
Section: Research In Major Livestock and Companion Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested that mesenchymal-like cell types are essential for cat enteroid growth. Recently, Tekes et al reported to have generated colon-derived organoids and studied host–pathogen interactions and immune response against feline enteric coronavirus [ 100 ].…”
Section: Research In Major Livestock and Companion Animalsmentioning
confidence: 99%
“…The respiratory, gastrointestinal, urogenital, and mammary epithelia, along with the skin, are the most important sites of contact with the outside environment, with intimate contacts with the respective microbiomes of these organs, including potential pathogens. While interaction with microbes has mostly been studied in organoid models of intestinal epithelia of different species [ 55 , 56 , 59 , 61 64 , 71 73 , 83 , 84 , 91 , 100 , 103 ], similar studies could be done in organoid models as have been done in human and rodents for the lung [ 121 ] and the mammary gland [ 122 ]. In the gut, the epithelium is constantly screening the contents of the intestinal lumen [ 123 , 124 ].…”
Section: Potential Uses Of Organoids In Livestock and Veterinary Resementioning
confidence: 99%
See 1 more Smart Citation
“…ASC-derived intestinal organoids have been derived from non-human species, including bat and feline. This has allowed the propagation of strains of coronaviruses directly from bats ( Tekes et al., 2020 ; Zhou et al., 2020 ). These efforts highlight how organoids can be exploited to study (species-specific) viruses with zoonotic potential.…”
Section: Organoids Go Viral To Study Infection Diseasesmentioning
confidence: 99%
“…Considering the presumable zoonotic background of SARS-CoV-2, researchers have for the first time established intestinal organoids from Chinese horseshoe bats suspected to be one of the natural reservoirs [ 112 ]. With the intestinal organoid culturing protocol also being applicable to other non-human mammalian species such as the cow [ 113 ], pig [ 113 , 114 ], dog [ 115 ], and cat [ 116 ], important strides have been made to consolidate our current pathophysiological understanding of zoonotic diseases. Combining the findings derived from intestinal organoids spanning different species will certainly be of added value for characterizing a broad spectrum of common zoonotic bacterial pathogens affecting the intestinal tract.…”
Section: Chances and Drawbacks Of Intestinal Organoidsmentioning
confidence: 99%